1971
DOI: 10.1136/bmj.3.5770.373-b
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone for anemia in maintenance dialysis.

Abstract: life of this important chemosterilizer, investigations should be undertaken with the polymeric,4 rather than the monomeric, form of glutaraldehyde.Full details of this work will be published elsewhere.-We are, etc.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the erythropoietic action of these hormones, several studies in the 1970s were designed to determine the effect of AND on the anemia of CRF (38)(39)(40)(41)(42)(43)(44)(45). These studies demonstrated that AND had a favorable effect on anemia in stable HD patients, some showing a dramatic response.…”
Section: Androgens and Renal Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the erythropoietic action of these hormones, several studies in the 1970s were designed to determine the effect of AND on the anemia of CRF (38)(39)(40)(41)(42)(43)(44)(45). These studies demonstrated that AND had a favorable effect on anemia in stable HD patients, some showing a dramatic response.…”
Section: Androgens and Renal Anemiamentioning
confidence: 99%
“…These studies demonstrated that AND had a favorable effect on anemia in stable HD patients, some showing a dramatic response. Nevertheless, the results varied greatly due to the heterogeneity of patients and the diversity of compounds used (40,41). Overall, before the advent of rHuEPO, AND were the mainstay of nontransfusional treatment for anemic patients on dialysis.…”
Section: Androgens and Renal Anemiamentioning
confidence: 99%